2017
DOI: 10.1007/s12094-017-1724-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting ERK/Mnk/eIF4E broadly sensitizes ovarian cancer response to chemotherapy

Abstract: Our work shows that ERK/Mnk/eIF4E activation is critically involved in ovarian cancer chemoresistance and inhibiting ERK/Mnk/eIF4E broadly sensitizes ovarian cancer response to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…The mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway and the Hippo pathway were reportedly associated with cell proliferation, differentiation, migration, senescence, and apoptosis [17][18] . Previous studies have shown that alteration of the MEK/ERK pathway is strongly implicated in ovarian cancer pathogenesis [19][20] . Dang et al, [21] reported that metformin combined with cisplatin inhibited cell viability and promoted apoptosis of human ovarian cancer cells by inactivating ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway and the Hippo pathway were reportedly associated with cell proliferation, differentiation, migration, senescence, and apoptosis [17][18] . Previous studies have shown that alteration of the MEK/ERK pathway is strongly implicated in ovarian cancer pathogenesis [19][20] . Dang et al, [21] reported that metformin combined with cisplatin inhibited cell viability and promoted apoptosis of human ovarian cancer cells by inactivating ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the MAPK signaling pathway is one of the most frequent events in cancer and affects many features inherent to malignant cells [32,46]. Most notably, high activity of the MEK1/2-ERK1/2 portion of the MAPK cascade directly promotes cell proliferation, survival, and drug resistance [31][32][33]47]. Furthermore, a number of studies reported that ERK1/2 activation occurs in CSCs [27] and is crucial for cell survival and proliferation in prostate, breast, and thyroid tumors [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cisplatin treatment of HGSOC cells results in further MEK1/2 pathway activation that persists in cisplatin-resistant cells. MEK1/2-ERK1/2 signaling inhibition in ovarian cancer cells is reported to sensitize them to chemotherapy [47], so MEK1/2 pathway hyperactivation could be a mechanism allowing HGSOC cells to overcome cytotoxic effects of cisplatin. Cisplatin-induced MEK1/2 activation in OVCAR8 and PEO4 cell lines established from recurrent tumors, which already obtained cisplatin resistance [52][53][54], suggests that repeated cisplatin treatment can further promote MEK1/2-ERK1/2 activity and associated chemoresistance in HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MNK1 knockdown and inhibition decreased ovarian cancer cell viability [57]. Liu et al demonstrated that MNK1 is involved in the resistance of ovarian cancer cells to chemotherapy [156]. They observed increased phosphorylation levels of ERK, MNK1, and eIF4E in ovarian cancer cells exposed to chemotherapy, as well as in ovarian cancer patients.…”
Section: Mnk In Other Solid Tumorsmentioning
confidence: 99%